1,2-Bis{2-[2-(trimethylsilyl)ethynyl]phenyl}ethane-1,2-dione - Sparrow, Christopher R. (International Union of Crystallography, 2012)
The title compound, C(24)H(26)O(2)Si(2), has C (2) crystallographic symmetry. The dihedral angle between the aromatic rings is 84.5 (2)°. The acetylene group is slightly non-linear, with angles at the acetylene C atoms of 175.7 (2) and 177.0 (2)°. In the crystal structure, only van de Waals interactions occur.